Pengaruh Desain Kemasan, Dan Variasi Produk Terhadap Minat Beli Konsumen (Studi Kasus Produk Burger Azzahra) - Kapriani, Kapriani; Jusman, Ikhsan Amar (DPW FORSILADI SULSEL, 2024)
In competitive business competition, companies need advantages to survive and succeed in the market. This advantage can encourage consumers to increase consumer buying interest. This research aims to determine the influence of packaging design and product variations on consumer buying interest. This type of research is explanatory research which explains cause and effect relationships between variables through hypothesis testing. This research used a sample of 75 respondents who live in Makassar City. The sampling technique uses random sampling. The data analysis method in this research uses instrument tests, classical assumption tests, and linear regression analysis. The results of this research show that packaging design has a positive and significant effect on Purchase Interest. Product variety has a positive and significant effect on Purchase Interest. Simultaneously, packaging design and product variations have a positive and significant effect on Purchase Interest.